2002
DOI: 10.1046/j.1365-2222.2002.01531.x
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupled regulation of leukotriene C4 synthase in platelets from aspirin‐intolerant asthmatics and healthy volunteers after aspirin treatment

Abstract: The results indicate that oral aspirin administration can lead to uncoupling of thromboxane A2-dependent negative feedback mechanisms, which may normally restrict the production of cysteinyl leukotrienes. This mechanism can be of potential interest in aspirin-induced asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Recent studies have shown that ongoing TBXA2 production can suppress LTC 4 synthase activity in eosinophils and smooth muscle cells, as well as in platelets, and is paralleled by suppressed levels of leukotriene [14,21]. These findings suggest that TBXA2 and TBXA2R polymorphisms may be related to leukotriene-dependent phenotypes of asthma such as AIA and asthma with EIB.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Recent studies have shown that ongoing TBXA2 production can suppress LTC 4 synthase activity in eosinophils and smooth muscle cells, as well as in platelets, and is paralleled by suppressed levels of leukotriene [14,21]. These findings suggest that TBXA2 and TBXA2R polymorphisms may be related to leukotriene-dependent phenotypes of asthma such as AIA and asthma with EIB.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to leukotriene, the role of TBXA2 in EIB has been poorly understood, but a recent study has demonstrated that attenuation of TBXA2 biosynthesis can lead to increased formation of leukotriene via uncoupling of LTC 4 synthase down-regulation in patients with AIA [14]. Thus, it is postulated that TBXA2 is a negative regulator of LTC 4 synthase, which leads to LT synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the aspirin challenge test aspirin further suppresses prostaglandin E 2 synthesis and uncouples the downregulation of LTC 4 S activity through inhibition of TXA 2 formation. 45 Additionally, arachidonic acid derived from adherent platelets activates 5-lipoxygenase in granulocytes and results in cysLT overproduction in patients with AERD (see Fig E3). 35 The results of our study suggest that antiplatelet therapy, especially with P-selectin antagonist, could be therapeutically beneficial in patients with AERD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that platelets from NSAID hypersensitive patients present a modified H2O2 metabolism [87] as well as some other indications of platelet involvement [88,89] but whether such alterations play a role in the generation of clinical symptoms is not ascertained.…”
Section: Cells Involved In Hypersensitivity To Nsaidsmentioning
confidence: 99%